2018
DOI: 10.1038/s41401-018-0024-8
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin attenuates toosendanin-induced hepatotoxicity through inducing the Nrf2/GCL/GSH antioxidant signaling pathway

Abstract: Toosendanin (TSN) is the main active compound in Toosendan Fructus and Meliae Cortex, two commonly used traditional Chinese medicines. TSN has been reported to induce hepatotoxicity, but its mechanism remains unclear. In this study, we demonstrated the critical role of nuclear factor erythroid 2-related factor 2 (Nrf2) in protecting against TSN-induced hepatotoxicity in mice and human normal liver L-02 cells. In mice, administration of TSN (10 mg/kg)-induced acute liver injury evidenced by increased serum alan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…Integrating liver biochemistry, network analysis and metabolomics results, PI3K/Akt pathway, primary bile acid biosynthesis as well as secretion, and glutathione metabolism might be involved in the anti-CHI effect of HGJD. Meanwhile, accumulated evidence has shown that activation of PI3K/Akt pathway could induce nuclear translocation of Nrf2, and then affect GSH synthesis, which was an important mechanism of nature product protection against hepatic oxidative injury ( Ma et al, 2015 ; Jin et al, 2019 ; Mukherjee et al, 2021 ). Therefore, western blotting was used to test and verify the effect of HGJD on PI3K/Akt/Nrf2 signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Integrating liver biochemistry, network analysis and metabolomics results, PI3K/Akt pathway, primary bile acid biosynthesis as well as secretion, and glutathione metabolism might be involved in the anti-CHI effect of HGJD. Meanwhile, accumulated evidence has shown that activation of PI3K/Akt pathway could induce nuclear translocation of Nrf2, and then affect GSH synthesis, which was an important mechanism of nature product protection against hepatic oxidative injury ( Ma et al, 2015 ; Jin et al, 2019 ; Mukherjee et al, 2021 ). Therefore, western blotting was used to test and verify the effect of HGJD on PI3K/Akt/Nrf2 signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, quercetin supplementation did not seem to modify the intestinal barrier permeability-associated markers TJP-1, TJP-2, and Ocln gene [ 12 ]. Jin et al reported that quercetin increased the expression of ZO-1 in rats treated with quercetin [ 43 ]. These two studies indicated that quercetin might affect the tight junction protein level of ZO-1but not Ocln.…”
Section: Resultsmentioning
confidence: 99%
“…Under normal conditions, Nrf2 is mainly located in the cytoplasm; under conditions of oxidative stress, Nrf2 translocates to the nucleus, binds to AREs and then initiates the activation of the endogenous anti-oxidative response to inhibit oxidative stress (32,33). Activation of Nrf2 signaling has been reported to increase cell anti-oxidative ability (34). HO-1 is a target gene of Nrf2, which is involved in regulating cellular ROS production and scavenging (35,36).…”
Section: Discussionmentioning
confidence: 99%